2015
DOI: 10.1016/j.chembiol.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

An Unaltered Orthosteric Site and a Network of Long-Range Allosteric Interactions for PNU-120596 in α7 Nicotinic Acetylcholine Receptors

Abstract: Summary Nicotinic acetylcholine receptors (nAChRs) are vital to neuronal signaling, are implicated in important processes such as learning and memory, and are therapeutic targets for neural diseases. The α7 nAChR has been implicated in Alzheimer’s disease and schizophrenia, and allosteric modulators have become one focus of drug development efforts. We investigate the mode of action of the α7-selective positive allosteric modulator, PNU-120596, and show that the higher potency of acetylcholine in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This saturating concentration was chosen on the basis of previously published data [ 33 , 37 ]. This modulator binds to a specific intrasubunit transmembrane allosteric site of α7 nAChR [ 47 50 ], so that the mutations inserted in the orthosteric ligand-binding site of α7 nAChR should not affect binding of PNU120596 to the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…This saturating concentration was chosen on the basis of previously published data [ 33 , 37 ]. This modulator binds to a specific intrasubunit transmembrane allosteric site of α7 nAChR [ 47 50 ], so that the mutations inserted in the orthosteric ligand-binding site of α7 nAChR should not affect binding of PNU120596 to the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…3; Table 1). The slope of the fluorination plot (20.16 6 0.03) is similar to that of acetylcholine (20.15 6 0.02) at TyrA for a7 (Marotta et al, 2015). This suggests a similar strength of interaction, despite the increased bulkiness of the ligand.…”
Section: Resultsmentioning
confidence: 57%
“…If the former mechanism were operative, it would complicate analysis of a silent agonist. However, we have previously shown that in a7 the type 2 PAM PNU-120596 does not alter the orthosteric binding site, as determined by detailed interactions with the native agonist ACh (Marotta et al, 2015). This was done by comparing the impact of a mutation on receptor function with or without the coapplication of the PAM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding interaction between nAChRs and some ligands were investigated experimentally [ 65 , 72 ]. Apart from developing the CDM, this study also investigated potential key binding interactions between human α7 nAChR-LBD and the ligands in the training set.…”
Section: Discussionmentioning
confidence: 99%